Voids-driven breakdown of the local-symmetry and Slater-Pauling rule in half-metallic Heusler compounds - Galanakis, I.; Sasioglu, E.; Bluegel, S.; Ozdogan, K. (AMER PHYSICAL SOC, 2014)
Slater-Pauling (SP) rules connect the magnetic and electronic properties of the half-metallic (HM) Heusler compounds. Employing first-principles electronic structure calculations we explore the validity of the SP rules in the case of transition from HM semi-Heusler compounds to various cases of HM full-Heusler compounds. We show that the coherent-potential approximation yields half-metallicity and thus a generalized version of the SP rules can be derived. On the contrary, supercell calculations, which are expected to describe the experimental situation more accurately, show that the energy gap considerably shrinks for the intermediate compounds and in several cases the half-metallicity is completely destroyed. The origin of this behavior is attributed to the voids, which influence the symmetry of the lattice.
Keywords: BAND-STRUCTURE; Materials Science; Physics